Tapering the Incident Field When Solving Problems of Electromagnetic Wave Scattering Over Finite-Size Random Surfaces - V. V. Leont’ev; M. A. Borodin (Известия высших учебных заведений России: Радиоэлектроника, 2021)
Introduction. An analysis of radio wave scattering over random surfaces frequently involves integral equations, which are solved by numerical methods. These methods are feasible only provided limited dimensions of the surface. The requirement of surface limitation leads to the appearance of edge currents, resulting in significant errors when calculating the radar cross section (RCS), particularly for grazing incident angles. The influence of edge currents is reduced by a function tapering the incident field amplitude. This function should satisfy the following requirements: to provide a low suppression of the field along the entire finite-size surface between its edges at the same time as decreasing the incident field amplitude to negligible values when approaching the edges. The incident field under the application of the tampering function should satisfy the wave equation with a minimum error. Although various tapering functions are applied for incident field amplitude (i.e. Gaussian, Thorsos, integral), none of them satisfies the aforementioned requirements.Aim. To suggest a novel function for tapering the amplitude of an electromagnetic wave incident on a perturbed finite-size surface when calculating RCS. In comparison with the known functions, the proposed function must satisfy the entire set of requirements.Materials and methods. A comparison of the proposed tapering function for incident field amplitude with the known tapering functions was performed, including the estimation of the error of satisfying the wave equation. To prove the applicability of the proposed tapering function, a mathematical modeling of the bistatic scatter diagram of a two-dimensional sea-like finite surface with a spatial Elfouhaily spectrum was carried out using Monte Carlo calculations in the Matlab environment.Results. Compared to the known tapering functions, the proposed tapering function satisfies the entire set of requirements. The results of mathematical modeling showed that the proposed function for tapering the incident field amplitude provides acceptable accuracy of estimating the RCS of finite-size random surfaces.Conclusion. A novel function for tapering the incident field amplitude was derived. This function reduces the influence of edge currents on the accuracy of RCS estimation of two-dimensional finite-size random surfaces, thus being instrumental for solving scattering problems.